Neutrophil to Lymphocyte Ratio (NLR) to Predict Mortality in Patients with Sepsis - Panezai , Taimoor Khan; Kakar , Kaleem Ullah; kakar , Inamullah; Zubair, Taham; Haider, Ali; Khan , Zafar Ahmed; kakar , Sana Ullah (Indus Journal of Bioscience Research, 2025)
Background: Sepsis, a leading cause of infection-related death, often results in high mortality despite advances in treatment. Early detection of high-risk patients is essential for improving outcomes. The Neutrophil-to-Lymphocyte Ratio (NLR) is a simple, inexpensive biomarker obtained from a complete blood count (CBC) that reflects the balance between inflammation and immune response. While NLR has been shown to predict outcomes in various conditions, its prognostic value in sepsis remains debated. Objective: This study aims to assess the predictive value of NLR for mortality in sepsis patients, determining whether higher NLR at hospital admission correlates with worse outcomes. Material and Methods: A retrospective analysis was conducted from July 2024 to December 2024 at tertiary care hospital in Quetta with 200 sepsis patients. NLR was calculated from CBC results at the time of admission, and patients were categorized based on survival and clinical outcomes. The relationship between NLR, disease severity, length of stay, and comorbidities was also examined. Results: Higher NLR values were significantly associated with increased mortality, prolonged hospital stays, septic shock, and higher mechanical ventilation requirements. Patients with NLR >10 had the highest mortality rate (83.3%). Conclusion: This study concludes that Neutrophil to Lymphocyte Ratio (NLR) has strong predictive value in sepsis severity and mortality. Higher NLR correlates with increased mortality, longer hospital stays, and more septic shock, with values above 10 being significant. It serves as a cost-effective biomarker, especially in resource-limited settings, aiding early detection and intervention. Future research should validate NLR thresholds and explore its role in sepsis monitoring and clinical protocols.